La incidencia de la normativa en la recaudación del Impuesto a la Renta de ingresos provenientes de herencias, legados y donaciones en la ciudad de Loja, periodos 2019- 2021 - Puchaicela Quezada, Lucy Adriana (2022)
The curricular integration work called THE IMPACT OF THE REGULATION ON INCOME TAX COLLECTION FROM INHERITANCES, LEGACY AND DONATIONS IN THE LOJA CITY, PERIODS 2019-2021 aims to analyze the changes in the regulations and their relationship with the collection of the tax at Loja city. In order to fulfill the development of the objectives, the research was based on the regulations applicable to the income tax of inheritances, legacies and donations in Ecuador and the modifications generated to better understand the scope of application of the tax; In addition, the data collected corresponding to the tax values collected in the city of Loja in relation to the fiscal periods 2019, 2020 and 2021 were analyzed, based on the general statistical database of collection of the Internal Revenue Service (SRI) where the taxes rest. data corresponding to values collected for taxes in each year, graphs and interpretation and comparative analysis of the collection in these periods were prepared; Finally, a practical case was proposed in which the law is considered according to the different modifications generated. This work is based on a qualitative approach given that it starts from the regulations and the bibliographical consultation regarding the field of taxes, to then delve into a quantitative analysis with the collection of the tax and the practical case raised. Subsequently, the conclusions and recommendations are presented based on the research carried out and the incidence of the regulations on the collection of the tax is determined. Keywords: Taxation, income tax, inheritance, donation, regulations.